2020
DOI: 10.2196/21486
|View full text |Cite
|
Sign up to set email alerts
|

Use of the HoloLens2 Mixed Reality Headset for Protecting Health Care Workers During the COVID-19 Pandemic: Prospective, Observational Evaluation

Abstract: Background The coronavirus disease (COVID-19) pandemic has led to rapid acceleration in the deployment of new digital technologies to improve both accessibility to and quality of care, and to protect staff. Mixed-reality (MR) technology is the latest iteration of telemedicine innovation; it is a logical next step in the move toward the provision of digitally supported clinical care and medical education. This technology has the potential to revolutionize care both during and after the COVID-19 pand… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 24 publications
3
56
0
3
Order By: Relevance
“…Although in-person visits are needed to provide timely routine care and for urgent and emergency situations, maintaining telehealth capacity is critical during the COVID-19 pandemic. Telehealth visits can facilitate patient triage, which can reduce the effect of patient surge on facilities, address limitations to health care access, conserve personal protective equipment, and reduce disease transmission ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although in-person visits are needed to provide timely routine care and for urgent and emergency situations, maintaining telehealth capacity is critical during the COVID-19 pandemic. Telehealth visits can facilitate patient triage, which can reduce the effect of patient surge on facilities, address limitations to health care access, conserve personal protective equipment, and reduce disease transmission ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Before the COVID-19 pandemic, lack of uniform coverage policies across insurers and states and obstacles to establishing telehealth in health systems (e.g., high startup costs, workflow reconfiguration, clinician buy-in, and patient interest) led to a slow adoption and use of telehealth services in the United States ( 8 ). Since the pandemic began, telehealth has been used to triage patients and reduce the impact of patient surge on facilities, address decreased access to health care, conserve PPE, and reduce the transmission of SARS-CoV-2 ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…2). with a decontamination protocol (10). The device and protocols were registered at our local institution with data governance agreed upon.…”
Section: Methodsmentioning
confidence: 99%
“…The use of HoloLens™ and similar MR devices have already been trialled in medical education speci cally for teaching anatomy (8,9). A recent pilot study at this centre demonstrated the use of HoloLens™ during the COVID-19 pandemic for direct clinical care reduced time exposure of staff caring for COVID-19 patients by 51.5% with an 83.1% reduction in PPE use (10).…”
Section: Introductionmentioning
confidence: 99%